Developing of Analytical Methods for Determination of Greywaters’ Detergent Content - Lós, Réka; Izbékiné Szabolcsik, Andrea; Bodnár, Ildikó (International Journal of Engineering and Management Sciences, 2018)
In our research we improved the technologies for the determinations of greywaters’ detergent content. We examined the quantity of anionic detergent (ANA) in synthetic greywater with Hyamine reagent using two-phased titrimetric method. We added to the synthetic greywater samples phenolphthalein indicator, acid mixed indicator and chloroform. After we shaked the mixture, and we got two separated phase. We titrated the mixture with cation active Hyamine reagent. The quantity of the chloroform and the quality of greywater samples (syntetic and real) were also changed in these experiment to determinate the actual ANA content. It was shown that the applied method is representative and reliable, too.